JUSTIFICATION OF MILK PRODUCTION TECHNOLOGY IN OPTIMIZING THE CONDITIONS OF LIVESTOCK - Yaremchuk , O. (EurasianUnionScientists, 2021)
Scientifically substantiated that in order to ensure optimal conditions for maintenance in the winter, the livestock of various sexual groups in one room it is expedient to carry out the reconstruction of the cows. The need for animals for animals in the room should be determined by the number of days to stay cows in the technological group depending on their physiological state and age, taking into account the general coefficients that are recommended by departmental technological design standards for specialized milk production.Investigated that unpredictable maintenance of dry cows in a separate isolated section, equipped with combinations, or binding in a separate isolated section provides more optimal values of air temperature, contributes to reducing the level of carbon dioxide by 0.06-0.08%, relative humidity By 16-20%, microbial pollution of air - in 2.1-2.3 times, the level of production noise - 6.5-7.9 times, improves the efficiency of the use of production space and internal equipment of the premises.